Carbon quantum dots anchored on 1, 2, 3, 5-tetrakis(carbazole-9-yl)-4, 6-dicyanobenzene for efficient selective photo splitting of biomass-derived sugars into lactic acid. Issue 15 (14th July 2022) - Yang, Xiaopan; Liu, Kangning; Ma, Jiliang; Sun, Runcang
Abstract : The application of photocatalysis in biomass reforming meets the needs of contemporary society for green and sustainable development, and its comprehensive utilization is appealing but challenging. Abstract : The application of photocatalysis in biomass reforming meets the needs of contemporary society for green and sustainable development, and its comprehensive utilization is appealing but challenging. Here, a novel metal-free photocatalyst (CQDs@4CzIPN) composed of carbon quantum dots (CQDs) anchored on 1, 2, 3, 5-tetrakis(carbazole-9-yl)-4, 6-dicyanobenzene (4CzIPN) was successfully prepared via a one-step hybrid evaporation–drying method. The sensitization of CQDs for 4CzIPN significantly broadened the absorption range of visible light by regulating the energy band structure, and also accelerated the migration/separation of photo-induced carriers. It is found that CQDs@4CzIPN exhibited excellent catalytic activity with a maximum lactic acid yield of 96.9%. CQDs@4CzIPN shows excellent stability and reusability in which the lactic acid yield retained 91.0% of its original value in the 5 th cycle; meanwhile, this CQDs@4CzIPN system exhibited excellent universality for the photocatalytic conversion of biomass-derived monosaccharides to lactic acid, but interestingly, the activities of pentoses are significantly better than those of hexoses. Moreover, ·O2 −, 1 O2, h + and ·OH were produced in the photocatalytic system, and their contents increased with visible light irradiation time. Oxidative active species capture experiments indicated that all of them are beneficial for lactic acid production, in which ·O2 − plays a leading role. This work provides a green approach for biorefining, and will inspire researchers to develop metal-free photocatalysts and apply them to photocatalytic biomass conversion.